Pemanfatan Limbah Baglog Jamur Tiram Menjadi Bahan Alternatif Briket di Desa Mojorejo Kecamatan Pungging - Hari Prastyo; Ahmad Sulthon; Muhammad Qhoiruman Afandi; Nur Azmil Muftakhoroh; Rita Efendi (JPMNT JURNAL PENGABDIAN MASYARAKAT NIAN TANA, 2026)
Mojorejo Village has the potential to develop oyster mushroom cultivation. However, with increasing production, mushroom baglog waste also increases and often becomes an environmental problem. Local residents lack the knowledge to utilize this waste optimally. To this end, outreach and training were conducted on making charcoal briquettes from mushroom baglog waste. This processing process allows baglog waste to be converted into a value-added product, namely charcoal briquettes. In addition to providing an effective waste management solution, this training also opens up new business opportunities for the community. The approach used in this activity is the ABCD (Asset Based Community Development) method, which focuses on empowering local potential. The results of the outreach showed that the resulting charcoal briquettes have good combustion quality and have the potential to be an environmentally friendly fuel. It is hoped that this training will reduce the accumulation of baglog waste and provide economic and environmental benefits for the residents of Mojorejo Village.